The Netherlandic presence in Ontario : pillars, class and Dutch ethnicity - Schryer, Frans J. (Waterloo, Ont. : Wilfrid Laurier University Press, 1998)
Annotation Schryer's central argument is that ethnic groups are as much modern "myths" as they are integral components of a socially constructed reality. Focusing on the large cohort of immigrants from the Netherlands and the former Dutch East Indies who arrived in Canada between 1947 and 1960, Schryer shows how the Dutch, despite a loss of ethnic identity and a high level of linguistic assimilation, replicated many aspects of their homeland. While illustrating and illuminating the diversity among immigrants sharing a common national origin, Schryer keeps sight of what is common among them. In doing so, he shows how deeply ingrained habits were modified in a Canadian context, resulting in both continuities and discontinuities. The result is a variegated image reflecting a multidimensional reality.
Front Matter -- Contents -- List of Figures -- List of Tables -- Foreword -- Preface -- Introduction -- Shifting Ethnicity -- Dutch Ethnicity: Genesis and Transformation -- Dutch Society and the Pillar System -- Postwar Migration: From Holland to Canada -- Transported Pillars (with Fieldnote Interludes) -- Adapting to Ontario -- The Spatial Distribution of Dutch-Canadians -- Dutch-Canadian Pluralism -- The Fate of the Catholic Pillar -- The Reformed Pillars -- Regional and Inter-National Networks -- Language Retention -- Negotiating Class Standing -- Gender and Dutch-Canadian Ethnicity -- Dutch Business -- The Dutch Credit Union Movement -- Dutch-Canadian Social and Cultural Associations -- The Elderly -- From Immigrants to Dutch-Canadians -- Dutch-Canadian Dispositions: Identity and Culture -- The Invisible Minority in the Vertical Mosaic -- A Reinterpretation of Immigration and Ethnicity -- Conclusion -- Glossary of Dutch Words and Acronyms (English) -- Notes -- Bibliography -- Index
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Dutch -- Ontario; Immigrants -- Ontario; Dutch Canadians -- Ontario; Néerlandais -- Ontario; Immigrants -- Ontario; Canadiens d'origine néerlandaise -- Ontario; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Dutch; Immigrants; Ontario; e-books.; Livres numériques.